Etika Mencari Ilmu dalam Islam (Kajian Psikologis – Sosiologis) - Nurul Faizatus Sholikah; Syamsurizal Yazid (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study discusses the importance of ethics in the process of seeking knowledge according to Islamic perspective, in a psychological and sociological approach. In Islam, seeking knowledge is an obligation for a human being, because in seeking knowledge it has high spiritual and moral values ​​where knowledge is not only able to elevate the individual's status but also contributes to social welfare. By using literature studies, this study analyzes the principles of ethics in learning and seeking knowledge including sincere intentions, patience, respect for teachers and fellow seekers of knowledge. These principles have a positive impact on the formation of individual character with morals and a harmonious society. The ethics of seeking knowledge in Islam emphasizes the importance of knowledge as a tool to achieve common welfare and build a just civilization.